AA. Zulfiqar. Comment on: Formosa V, Lorusso G, Lentini G, Terracciano E, Gentili S, Liotta G. Multidimensional Short Tools to assess frailty: a narrative review. (Ann Ig 2022 Mar 18. doi: 10.7416/ai.2022.2516. Online ahead of print)r - Zulfiqar, Abrar-Ahmad (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Once read the paper by Formosa et al in Ann Ig 2022 Mar 18. Online ahead of print, where the Authors ask for more studies to assess validity and reliability of the short tool to evaluate frailty proposed by me, through this letter I intend to demonstrate that its validity and reliability have been proved by a series of applications already published in the last past months.